Pentingnya Kebijakan Fiskal dalam Mendukung Pembangunan Berkelanjutan (Jurnal Kendali Akuntansi, 2024)
The aim of this research is to determine the level of importance of fiscal policy in supporting sustainable development and maintaining the stability of the Indonesian economy. The definition of fiscal policy is a series of actions taken by the government to maintain the stability of state expenditure and income with the aim of encouraging healthy economic growth. where in carrying out these actions the instruments used include: taxes, spending, public bonds and budget allocations. The research method used is a literature study of articles, journals and documents relevant to fiscal policy starting from taxation, APBN public bonds and budget allocations.. The data used is data from two previous researchers and financial projection data originating from credible government publications. The results obtained show that the important role of fiscal policy in supporting sustainable development is the government's right to regulate state revenues and expenditures in order to maintain the stability of the country's economy.